Design and Implementation MPPT-CPG for Constant Power Battery Charger - Farah Namira Fajrianingrum; Renny Rakhmawati; Eka Prasetyono (Department of Electrical Engineering ITS and FORTEI, 2022)
The power produced by photovoltaic is very dependent on irradiation conditions and temperature so that the power can be low or high. The load cannot work if the power is low, but it harms the load if the power is too high. Two modes are used for this system, they are MPPT and CPG mode. When PV power is less than limit power (Plimit), then it works on MPPT mode. The MPPT finds maximum power, then if PV power reaches Plimit or more, it works on CPG mode. During CPG mode, SEPIC converter output power is maintained constant at Plimit so the battery can be charged using the Constant Power Method. The Algorithm used for each mode is the variable Step Size Climbing. The Variable Step Size Hill-Climbing on MPPT performs maximum power according to irradiation conditions. Variables Step Size Hill-Climbing on CPG stabilizes the output power value of SEPIC being constant to charge the battery using the power constant method by keeping the power as constant as its limit power, voltage and current electricity bring into line with charge conditions. The results of the hardware integrated test for MPPT-CPG, the Variable Step Size Hill Climbing algorithm can search for the maximum power point (MPP) generated by PV and can produce an output power of 27.97 W in average.